Expert-Group Practical Advice on Insulin Initiation and Titration for Patients with Type 2 Diabetes in the Gulf Region - Mohammed Hassanein; Walid Al Dahi; Husain Taha Radhi; Abdulraouf AIMahfouz; Juma Al Kaabi; Abdulmuhsen Alshammari; Abdullah Alfutaisi; Mussa H. AlMalki; Rayaz Malik (Dubai Diabetes and Endocrinology Journal)
The type 2 diabetes mellitus (T2DM) management represents a major challenge in the Gulf region. Hyperglycemia is a major risk factor for microvascular and macrovascular complications and increased mortality. Early dietary and lifestyle changes alongside a step-wise targeted pharmacological approach to achieve a glycated hemoglobin (HbA1c) level of <7% are recommended to limit these complications. However, achievement of this HbA1c target remains a major challenge, especially in the Gulf region. Both physician and patient-led barriers limit timely initiation and titration of insulin. An expert-group advisory committee reviewed the current guideline recommendations, strategized best practice, and curated clinical practical advices to enable primary-care physicians to optimally initiate and titrate insulin in patients with T2DM.